2012
DOI: 10.1371/journal.pgen.1002685
|View full text |Cite
|
Sign up to set email alerts
|

Using Whole-Genome Sequence Data to Predict Quantitative Trait Phenotypes in Drosophila melanogaster

Abstract: Predicting organismal phenotypes from genotype data is important for plant and animal breeding, medicine, and evolutionary biology. Genomic-based phenotype prediction has been applied for single-nucleotide polymorphism (SNP) genotyping platforms, but not using complete genome sequences. Here, we report genomic prediction for starvation stress resistance and startle response in Drosophila melanogaster, using ∼2.5 million SNPs determined by sequencing the Drosophila Genetic Reference Panel population of inbred l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
222
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 190 publications
(246 citation statements)
references
References 56 publications
(108 reference statements)
17
222
7
Order By: Relevance
“…The results differ both from those reported by Meuwissen and Goddard (2010), based on simulated data, and those from Ober et al (2012), based on real data from Drosophila. Meuwissen and Goddard (2010) simulated QTL allele frequencies following that expected under a neutral model.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results differ both from those reported by Meuwissen and Goddard (2010), based on simulated data, and those from Ober et al (2012), based on real data from Drosophila. Meuwissen and Goddard (2010) simulated QTL allele frequencies following that expected under a neutral model.…”
Section: Discussioncontrasting
confidence: 99%
“…This increase in accuracy has not been observed in real data as yet. Ober et al (2012) found no increase in accuracy of predictions for quantitative traits in 157 inbred lines of Drosophila melanogaster, when comparing predictions from a dense SNP panel or the full-genome sequence. However, the small size of that data set makes it difficult to draw definitive conclusions about the value of full-genome sequence data in genomic predictions-as the effect of the causative mutations on the quantitative traits may be very small, given the genetic architecture observed for many quantitative traits (for example, Kemper et al (2011) and Stahl et al (2012)), large numbers of individuals will still be required to estimate these effects accurately.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Variance components (σ 2 ) were calculated from the full models fitting genotype, genotype‐by‐sex and replicate vial as random effects. Broad‐sense heritabilities can be calculated as variance due to genotype divided by the full variance (Ober et al., 2012) and are marked in the table with bold numbers. *p < .05, **p < .01, ***p < .001.…”
Section: Resultsmentioning
confidence: 99%
“…For the log‐transformed DT data, the model included the fix effect of sex and the random effect of replicate vial as well: Y ijkl  =  μ  + L i   + S j   + L i S j   + V k   +  ε ijkl . Broad‐sense heritability (repeatability) was calculated as H 2  =  normalσnormalL2false/false(normalσnormalL2+normalσnormalLS2+normalσnormalV2+normalσnormalresidual2) for DT (Ober et al., 2012), and as 4*normalσnormalL2false/false(normalσnormalL2   +  π 2 /3) for EAV (Davies, Scarpino, Pongwarin, Scott, & Matz, 2015), where σL2 is the variance of the random line effect and π 2 /3 is the variance of the logistic distribution. To eliminate the scale effects and therefore have a comparable measure of variability of the traits across the densities, we used coefficients of variation (CVs; Houle, 1992).…”
Section: Methodsmentioning
confidence: 99%